KAJIAN YURIDIS TENTANG REGULASI PEMEKARAN DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH BESERTA PERATURAN PELAKSANA (Studi Pembentukan Provinsi Kapuas Raya di Kalimantan Barat) - Redin Redin (Universitas Kapuas Sintang, 2013)
In the context of regional expansion, Article 4 (paragraph 3) of Act. Number 32 of 2004 about Regional Government give assurance that the possibility of the formation of a merger of several local or regional sections of biting or expansion of an area into two regions or more. By referring to Act. No. 32 of 2004 and the procedure refers to Government Regulation Number 129 of 2000 about Formation Conditional and Criteria for Expansion, Elimination and Regional Merger, the administration proposed splitting of the Province of West Kalimantan Kapuas Raya with the formation of the Province are complete and are qualified conditions of administrative, technical and physical territoriality. By the Governor of West Kalimantan, give information to the Commission II Advisory Council of the Republic of Indonesia. As suggested in the current domain and the Central Government Advisory Council of the Republic of Indonesia came to pass repeal of Government Regulation Number 129 of 2000 which has been used as a guideline proposed for establishing the Province of Kapuas Raya and replaced by Government Regulation Number 78 of 2007 on Procedures for Formation, Elimination and Region Merging. Cancellation of Government Regulation Number 129 of 2000, has implications for certainty of law (legality) the completeness of the proposed administrative division of West Kalimantan Province. With the Government Regulation Number 129 of 2000 jo. Government Regulation Number 78 of 2007 then, needs to be done in a normative study of the Act. 32 of 2004 by Government Regulation Number 129 of 2000 and Government Regulation Number 78 of 2007. Based on the result of analysis the problems examined, it is known that the proposed of the Province of West Kalimantan Kapuas Raya based on existing provisions in the Government Regulation Number 129 of 2000. While the enactment of Government Regulation Number 78 of 2007 automatically revoke the previous government regulation and no longer valid, because the Argumentum contrario Government Regulation Number 78 of 2007 Concerning Formation, Elimination and Regional Merger may not be used against the events referred to regulations occurred prior to the otherwise applicable government regulation. Based on the results the Government recommended, given the division of the Province of West Kalimantan province with the establishment of Kapuas Raya domain was already in the Central Government to get the draft Law Kapuas Raya Province Formation of Advisory Council of the Republic of Indonesia, the final step until now realized yet, in expect for the entire Local Government and Regional Representatives Council of the District Sintang, Sanggau, Sekadau, Melawi and Kapuas Hulu regency or provincial government more intensive approach the House of Representatives Commission II of the Republic of Indonesia and the Minister of Foreign Affair.